The achiasmia spectrum: congenitally reduced chiasmal decussation. Issue 10 (16th September 2005) - Sami, D A; Saunders, D; Thompson, D A; Russell-Eggitt, I M; Nischal, K K; Jeffery, G; Dattani, M; Clement, R A; Liassis, A; Taylor, D S
Abstract : Aim: To describe the clinical spectrum of achiasmia, a congenital disorder of reduced relative decussation at the optic chiasm. Methods: A retrospective case note and patient review of nine children (four boys). Achiasmia was defined by the combination of a characteristic asymmetry of the monocular visual evoked potential (VEP) response to flash and neuroimaging showing reduced chiasmal size. Results: Three of the children had an associated skull base encephalocele with agenesis of the corpus callosum. In two patients achiasmia was associated with septo-optic dysplasia. Three patients had no neuroimaging abnormalities other than reduced chiasmal size and have no known pituitary dysfunction. One child had multiple physical deformities but the only brain imaging abnormality was reduced chiasmal size. Conclusions: Some children with disorders of midline central nervous system development, including septo-optic dysplasia and skull base encephaloceles, have congenitally reduced chiasmal decussation. Reduced relative decussation may co-exist with overall chiasmal hypoplasia. Children with an apparently isolated chiasmal decussation deficit may have other subtle neurological findings, but our clinical impression is that most of these children function well.